Telur Trichuris trichiura pada Bagian Luar Tubuh Lalat Musca domestica sebagai Penyebab Penyakit Trichuriasis pada Manusia - Kinsay Maura Larasati; Soebaktiningsih Soebaktiningsih; Bahrudin Bahrudin; Febri Endra Budi Setyawan (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Background: Musca domestica is the most common fly species and spreading around the world also act as mechanical vectors various pathogenic agent (virus, bakteri, parasite, one of them is Trichuris trichiura). Human will suffer from Trichuriasis if they ingest food ordrinks contaminating Trichuris trichiura eggs. The prevalence of Trichuriasis is still high and it affects children more often because lack of hygiene. Purpose: to determine the role of Trichuris trichiura eggs on the body surfaces of Musca domestica thatcauses Trichuriasis in humans.Methods: Literature review by retrieving library resources from 39 journals and 2textbooksselected by using the criteria of accredited national journals sintaand reputable international journals and indexed scopus and non-scopus published by 2016.Results: From some experimental studies, Musca domestica carried Trichuris trichiura eggs on the outer body surfaces, as mechanical vectors potential for spreading Trichuriasis.Conclusion: Trichuris trichiura eggs carried by outer body surfaces of Musca domestica can causes serious health problem in humans, has potential cause Trichuriasis disease. Good control and education are needed to prevent Trichuriasis disease